Формування соціальної компетентності дітей старшого дошкільного віку - Калініч, Сергій Іванович (My University, 2024)
Тема кваліфікаційної роботи «Формування соціальної компетентності дітей старшого дошкільного віку» досліджувалася на теоретичному та емпіричному рівнях. Результати вивчення представлено у двох розділах роботи. На теоретичному рівні схарактеризовано стан розробки проблеми вітчизняними та зарубіжними фахівцями; розкрито особливості розвитку соціальної компетентності у дошкільному дитинстві; обґрунтовано педагогічні умови оптимізації процесу виховання вказаної інтегральної якості у закладі дошкільної освіти. З метою розв»язання емпіричних завдань дослідження розроблено програму й методику констатувального експерименту; визначено критерії, показники та структурні компоненти вихованості у дітей 5-7 років соціальної компетентності; описано рівні сформованості даної якості у досліджуваних старшого дошкільного віку; розроблено систему формування соціальної компетентності , обґрунтовано педагогічні умови оптимізації освітнього процесу, розкрито методи виховання даної моральної якості у дітей 5-7 років.
The topic of the qualification work "Formation of social competence of older preschool children" was studied at the theoretical and empirical levels. The results of the study are presented in two sections of the work. At the theoretical level, the state of development of the problem by domestic and foreign specialists is characterized; the peculiarities of the development of social competence in preschool childhood are revealed; the pedagogical conditions for optimizing the process of education of the specified integral quality in the preschool education institution are substantiated. In order to solve the empirical tasks of the research, the program and methodology of the ascertaining experiment were developed; the criteria, indicators and structural components of upbringing in children 5-7 years of social competence are determined; the levels of formation of this quality in the studied older preschoolers are described; a system of social competence formation was developed, pedagogical conditions for optimizing the educational process were substantiated, and methods of raising this moral quality in 5-7-year-old children were revealed. Key words: personality development, social competence, socialization of a child in preschool education, criteria of formation and pedagogical conditions for the development of social competence.
Keywords: розвиток особистості; соціальна компетентність; соціалізація дитини у ЗДО; критерії сформованості соціальної компетентності